An analysis of leader's bases of power and knowledge management practices: A conceptual approachn - Jayasingam, Sharmila; Jantan, Muhamad; Ansari, Mahfooz (2007)
Knowledge management (KM) is considered one of the critical success factors for the survival of organizations in the present world. With the growing importance of KM, organizations are trying to outdo one another in establishing a sound KM system by investing huge amounts in information technology. However, despite the adoption of the most excellent information technology and access to the richest information sources, surveys indicate that KM systems are failing at an equal pace as the rate of implementation. The underlying reason for the failures would be the inability of organizations to realize that the success of the KM system does not solely rely on technology, but also on the ability to motivate organization members to contribute and participate actively in creating, sharing and using knowledge. In order to change people's behavior and create acceptance, commitment and motivation among knowledge workers, leadership plays a crucial role. Although most research highlights leadership as an essential success factor for KM initiatives, it is unclear as to what leadership characteristics (in the form of social power) are needed in a knowledge-based organization. This paper is a conceptual paper that intends to discuss the potential impact of leaders' bases of power in encouraging KM practices that cultivates improved organizational performance.